Machine Learning Algorithm for Global Challenges in Businesses - Saffari, Gholamreza (International journal of industrial engineering and operational research, 2024)
This paper explores the significance of machine learning algorithms in addressing global challenges faced by businesses. It examines various machine learning algorithms and their suitability for tackling these challenges. The paper presents a comprehensive literature review to understand the current state of research in this area. The methodology section outlines the process of selecting and implementing suitable algorithms for addressing specific business problems. Numerical results are presented to demonstrate the effectiveness of machine learning algorithms in solving global challenges. Finally, the conclusions draw insights on the potential of machine learning algorithms and provide recommendations for businesses to harness their capabilities effectively.